A Quasi-Hilbert Space and Its Properties - Al-Delfi, Jawad (Al-Qadisiyah Journal of Pure Science, 2021)
This paper studies concept of a quasi-inner product space and its completeness to get and prove some properties of quasi-Hilbert spaces. The best examples of this notion are spaces where 0<p<∞.